Study on Flow Structure Characteristics Along the Latticework Duct Subchannels and Classification Boundary Prediction - Minlong Li; Huishe Wang; Ke Yang; Rongguo Yu; Jingze Ton (Aerospace)
To reasonably divide the types of flow units along the latticework subchannel, one must prepare for the establishment of a one-dimensional fluid network model of the latticework in the middle region of the turbine blade. The characteristics of the flow structure along the latticework subchannel were studied by numerical simulation. The effects of rib angle (15–45°), the ratio of rib width to rib spacing (0.3–1.0), and inlet Reynolds umber (21,000–80,000) on the flow structure along the subchannel are summarized. The results indicated that the ratio of rib width to rib spacing and inlet Reynolds number had no effect on the distribution position of each flow unit in the subchannel. The change of rib angle did not change the flow structure type along the subchannel. The longitudinal vortex was mainly formed by one turning vortex and two detached vortices. The narrowing of the turning channel will cause the turning vortex to induce a secondary longitudinal vortex. There were five kinds of flow structures along the subchannel: transverse vortex zone (entrance of the inlet section), uniform flow zone (inlet section), longitudinal vortex generation zone (turning channel section), longitudinal vortex zone (turning channel section), and longitudinal vortex free development zone (outlet section). This finding provides support for the selection of empirical formulas for each module in the one-dimensional modeling of subchannels. Finally, the boundary prediction equations of each flow structure in the subchannel were established, and the average prediction error was less than 10%. The rationality of the flow structure division along the latticework subchannel was improved, and the modeling efficiency of the latticework one-dimensional model was optimized.